(untitled) (New York, NY., 2003)
This reference details particle characterization, dynamics, manufacturing, handling, and processing for the employment of multiphase reactors, as well as procedures in reactor scale-up and design for applications in the chemical, mineral, petroleum, power, cement and pharmaceuticals industries. The authors discuss flow through fixed beds, elutriation and entrainment, gas distributor and plenum design in fluidized beds, effect of internal tubes and baffles, general approaches to reactor design, applications for gasifiers and combustors, dilute phase pneumatic conveying, and applications for chemical production and processing. This is a valuable guide for chemists and engineers to use in their day-to-day work.
Keywords: Fluidization